2017
DOI: 10.3399/bjgp17x692525
|View full text |Cite
|
Sign up to set email alerts
|

Does aerobic exercise reduce postpartum depressive symptoms? a systematic review and meta-analysis

Abstract: This systematic review provides support for the effectiveness of exercise in reducing postpartum depressive symptoms. Group exercise, participant-chosen exercise, and exercise with co-interventions all may be effective interventions. These results should be interpreted with caution because of substantial heterogeneity and risk of bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 31 publications
0
56
0
1
Order By: Relevance
“…Complementary and alternative medicine treatments (for example, folate, s-adenosylmethionine, massage and acupuncture) are not well-supported by evidence. 198 However, using aerobic exercise for postpartum depression was recently examined in a systematic review and has good supporting evidence for mild symptomatology 199 . ECT can be considered in severe or treatment-refractory cases of depression.…”
Section: [H2] Mood Disorders and Anxietymentioning
confidence: 99%
“…Complementary and alternative medicine treatments (for example, folate, s-adenosylmethionine, massage and acupuncture) are not well-supported by evidence. 198 However, using aerobic exercise for postpartum depression was recently examined in a systematic review and has good supporting evidence for mild symptomatology 199 . ECT can be considered in severe or treatment-refractory cases of depression.…”
Section: [H2] Mood Disorders and Anxietymentioning
confidence: 99%
“…On the other hand, meta-analyses and systematic reviews support the notion that “exercise as medicine” ( Pedersen and Saltin, 2015 ; Gerber et al, 2016 ; Hallgren et al, 2016 ) also benefits patients with mental disorders such as major depressive disorders ( Knapen et al, 2015 ; Stubbs et al, 2016 ; Bailey et al, 2017 ; Krogh et al, 2017 ; Schuch et al, 2017 ; Sukhato et al, 2017 ; Vancampfort et al, 2017a ; Wu et al, 2017 ), including among elderly patients ( Mikkelsen et al, 2017 ; Perez-Lopez et al, 2017 ), post-partum depression ( McCurdy et al, 2017 ; Poyatos-Leon et al, 2017 ; Pritchett et al, 2017 ; Saligheh et al, 2017 ), bipolar disorders ( Vancampfort et al, 2017a ), post-traumatic stress disorders ( Rosenbaum et al, 2015 ; Vancampfort et al, 2016 ), anxiety disorders ( Gordon et al, 2017 ; Stubbs et al, 2017 ; Vancampfort et al, 2017b , c , d ), and psychosis/schizophrenia ( Pajonk et al, 2010 ; Keller-Varady et al, 2017 ; Mittal et al, 2017 ; Tarpada and Morris, 2017 ; Vancampfort et al, 2017a ), while among patients with substance use disorders the evidence supporting regular exercise is weaker [alcohol use disorder: ( Vancampfort et al, 2015a ; Hallgren et al, 2017 ); tobacco use disorder: ( Ussher et al, 2014 )].…”
Section: Introductionmentioning
confidence: 98%
“…[12][13][14] Exercising also brings other benefits such as improved overall fitness, opportunities to socialise, and the potential for reduction in feelings of depression, all of which may help to moderate the symptom profile in PMS. 2,15,16 A previous systematic review of this topic found low-level evidence to support the recommendation of exercise for symptom management in PMS. 17 It is this review that provides the supporting basis for the RCOG recommendation in its PMS guidelines.…”
Section: Introductionmentioning
confidence: 99%